A windable and stretchable three-dimensional all-inorganic membrane for efficient oil/water separation. Issue 1 (December 2017) - Wang, Kui; Han, Dong; Yiming, Wubulikasimu; Ahzi, Said; Abdel-Wahab, Ahmed; Liu, Zhaoyang
Abstract There is strong interest in windable and stretchable membranes to meet the technological demands of practical water treatments. Oil/water separating membranes of this type is still significantly underdeveloped. Here, we reported a windable and stretchable membrane with three-dimensional structure for efficient oil/water separation. This membrane is made of ZnO nanorods arrays conformally grown on woven carbon microfibers. This three-dimensional architecture endows the fabricated membrane with highly windable and stretchable properties, at the same time ensures ZnO nanorods fully exposed outwards on the membrane surface. Due to its superior hydrophilicity and oleophobicity of ZnO nanorods, this all-inorganic membrane exhibits outstanding antifouling property, with the foulants on membrane surfaces easily removed by simple physical cleaning without chemicals. The membrane can effectively separate both oil/saline-water mixtures and oil-in-water emulsions, solely driven by gravity, with extremely high permeation flux of 20933.4 L m−2 h−1 and high separation efficiency over 99%.